Gender Differences in Trust and Reciprocity - Ananish Chaudhuri; Lata Gangadharan (Wellesley College, Department of Economics, 2002)
We use the investment game introduced by Berg, Dickhaut and McCabe (1995) to explore gender differences in trust and reciprocity. In doing so we replicate and extend the results first reported by Croson and Buchan (1999). We find that men exhibit greater trust than women do while women show much higher levels of reciprocity. Trusting behavior is driven strongly by expectations of reciprocation. We posit that the lower levels of trust exhibited by women may be attributed to a higher degree of risk aversion. We derive estimates for the risk aversion parameter for both men and women.
Keywords: D83; C91; C72; 330; Gender Differences; Trust; Reciprocity; Risk Aversion; Experiments; Vertrauen; Geschlecht; Social Capital; Experiment; Theorie; reciprocity